Ocimum gratissimum essential oil improved the health, innate immunity and resistance to Aeromonas hydrophila infection in Pseudoplatystoma reticulatum - da Silva, Leonardo Augusto; Pilarski, Fabiana [UNESP]; Chaves, Francisco Célio Maia; Chagas, Edsandra Campos; Fernandes, Carlos Eurico; Libanori, Maria Clara Miguel; Pereira, Scheila Anelise; Martins, Maurício Laterça; de Campos, Cristiane Meldau (Universidade Estadual de Londrina, 2021)
The essential oil of alfavaca (Ocimum gratissimum) contains important compounds, such as 1.8-cineol and eugenol. This study evaluated the effects of diets containing alfavaca essential oil on the zootechnical performance, plasma glucose, leukocyte respiratory activity, haematology, and intestinal histomorphometry in “cachara” (Pseudoplatystoma reticulatum) challenged with Aeromonas hydrophila. A total of 300 juvenile fish, with an average total length of 14.98 ± 0.28 cm and average weight of 18.84 ± 1.22 g, distributed in 20 tanks of 80 L, were fed twice a day with a diet containing essential oil at 0.5, 1.0, or 1.5% or without its inclusion in five replicates. After 45 days, blood collection and mid-intestinal bowel were sampled, before a challenge with Aeromonas hydrophila was performed. The fish supplemented with 1.0% of essential oil presented better weight gain, mean corpuscular volume, concentration of thrombotic and neutrophils, respiratory activity of leukocytes, and height of villi (p < 0.05) when compared to other groups. The cumulative mortality response was lower for fish fed 1.5% essential oil of alfavaca diets. Thus, the use of alfavaca essential oil is recommended in the diet of cachara catfish (P. reticulatum) at the level of up to 1.0% for 45 days for improvements in the zootechnical, haematological, and intestinal histomorphometric parameters.
Óleo essencial de Ocimum gratissinum melhorou a saúde, imunidade inata e resistência à infecção por Aeromonas hydrophila em Pseudoplatystoma reticulatum
Keywords: Bacterial experimental infection; Blood alterations; Immunological response; Native fish; Performance